HOLY QUR'AN RECITATION TO OVERCOME ANXIETY - Indri Seta Septadina; Hendra Sutysna; Dalilah Dalilah (International Journal of Islamic and Complementary Medicine, 2020)
Anxiety is an uncomfortable, pleasant, indistinct and pleasant feeling with autonomic symptoms. Many internal and external factors cause anxiety in a person. Non-pharmacological intervention anxiety that has lower side effects is safer and can be used for a more extended period compared to anti-anxiety drugs. The recitation of the Al-Qur'an generates alpha waves, which are waves that appear when someone is relaxing. Increased alpha waves can reduce symptoms of anxiety.